2019
DOI: 10.1111/jpy.12866
|View full text |Cite
|
Sign up to set email alerts
|

Leptothoe, a new genus of marine cyanobacteria (Synechococcales) and three new species associated with sponges from the Aegean Sea

Abstract: Cyanobacterial diversity associated with sponges remains underestimated, though it is of great scientific interest in order to understand the ecology and evolutionary history of the symbiotic relationships between the two groups. Of the filamentous cyanobacteria, the genus Leptolyngbya is the most frequently found in association with sponges as well as the largest and obviously polyphyletic group. In this study, five Leptolyngbya‐like sponge‐associated isolates were investigated using a combination of molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 65 publications
(144 reference statements)
1
30
0
1
Order By: Relevance
“…Stackebrandt (2006) changed the cut‐off points to higher values which was even more strictly supported by the cut‐offs proposed in Yarza et al (2014; 98.7% for species, 94.5% for genera). Many recent studies have shown that cyanobacterial species have distinct morphological features even above a similarity level of 97.5% (Osorio‐Santos et al 2014, González‐Resendiz et al, 2019, Konstantinou et al 2019) and some authors even suggest a cut‐off level for, for example, genera within the Nostocales of 98% similarity and for species of <99% (Kaštovský et al 2014). An additional and recent example for comparable cut‐off levels in pleurocapsalean cyanobacterial species is the newly described cyanobacterium Odorella benthonica that shows 99.92% similarity to Pleurocapsa minor JQ070059 and is separated by striking morphological and ecological differences (Shalygin et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Stackebrandt (2006) changed the cut‐off points to higher values which was even more strictly supported by the cut‐offs proposed in Yarza et al (2014; 98.7% for species, 94.5% for genera). Many recent studies have shown that cyanobacterial species have distinct morphological features even above a similarity level of 97.5% (Osorio‐Santos et al 2014, González‐Resendiz et al, 2019, Konstantinou et al 2019) and some authors even suggest a cut‐off level for, for example, genera within the Nostocales of 98% similarity and for species of <99% (Kaštovský et al 2014). An additional and recent example for comparable cut‐off levels in pleurocapsalean cyanobacterial species is the newly described cyanobacterium Odorella benthonica that shows 99.92% similarity to Pleurocapsa minor JQ070059 and is separated by striking morphological and ecological differences (Shalygin et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Since metagenomics studies suggest that microeukaryotic communities in sponges are largely derived from seawater (Cleary 2019) and in combination with the worldwide distribution of A. leptochaete, we could hypothesize that Dysidea avara acquired A. leptochaete from the surrounding Aegean seawater. The photosymbiont community of the sponge D. avara in the Aegean Sea also comprises cyanobacteria such as the recently described Leptothoe spongobia (Konstantinou et al 2019). Previously, Chlorophyta belonging to the genus Desmodesmus have been isolated from the marine sponge Halichondria (Halichondria) panicea (Kravtsova et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The Mediterranean Sea remains understudied as regards sponge-associated eukaryotic microalgae, whereas no information exists for the eastern Mediterranean and the Aegean Sea. Our recent research in the area, which revealed new diversity of photosynthetic prokaryotes associated with Aegean sponge species (Konstantinou et al 2018(Konstantinou et al , 2019(Konstantinou et al , 2020, brought to light several photosynthetic eukaryotes from the same sponges. In this paper, we aim to explore and characterize the diversity of sponge-associated photosynthetic eukaryotes based on a culture-dependent method.…”
mentioning
confidence: 99%
“…Phylogenetic relationships among coccoid and filamentous cyanobacteria strains were examined separately, strictly referring to the species and sequence selection reported by Konstantinou and coll. [14,20,39] and refined by Gkelis and coll. [13]…”
Section: Molecular Analysismentioning
confidence: 99%